(untitled) (Journal Of Educational and Psychological Researches, 2022)
Due to the increasing number of people with in Iraq, it has become necessary to treat seriously this problem, which was not considered significantly to the best of researcher knowledge. Thus, the current research aims to construct a scale to measure the physical down syndromes, which distinguish them from others. It consisted of (39) items. The researcher has presented some related literature that addressed the current problem